Implementation of RShiny in Developing Interactive Learning Media for Analysis of Variance (ANOVA) - Simarmata, Justin Eduardo; Chrisinta, Debora; Purnomo, Miko (Journal of Research in Mathematics Trends and Technology, 2025)
Effective learning is significantly influenced by the methods and media used in the teaching and learning process. However, many students still struggle to understand mathematical concepts due to the limited availability of interactive learning media. Therefore, this study aims to develop and evaluate the effectiveness of a technology-based interactive learning application designed to enhance students' understanding. The development of this application follows several stages, including needs analysis, design, implementation, testing, and evaluation. The application offers various features, such as interactive materials, practice exercises, and visual simulations, to facilitate better comprehension of concepts. The data used in this study consists of pretest and posttest results from 30 students who were given a series of basic questions, including calculating the mean, standard deviation, and performing simple statistical tests. Analysis using the Paired t-Test indicates a significant increase in posttest scores compared to pretest scores (p-value = 3.522e-08). Data visualization in the form of boxplots and line charts also demonstrates a trend of improved student performance after using the application. Thus, this study confirms that the developed interactive application is effective in enhancing student learning outcomes.